Commentary: Attitudes of local population of tourism development impacts: Evidence from Czechia - Dias, Á.; Patuleia, M. (Frontiers in Psychology, 2021)
The impact of tourism on small communities located in peripheral areas, many of them rural, was the subject of the study conducted by Linderová, Scholz and Almeida (2021). The authors advocate the critical participation of the local community in tourism development. This is a very important issue that has been widely debated in the context of the pandemic and post-pandemic resulting from COVID-19. Indeed, this strongly adverse context for tourism is also a time to rethink pre-pandemic tourism, massive and generally damaging to the tourism destination, towards more sustainable and inclusive approaches for the local community (Hall, Scott & Gössling, 2020).